Evaluación del proceso de remoción de hierro por medio de la Zeolita Clinoptilolita en el tratamiento de aguas residuales industriales (2016)
In this work the iron removal process develops in wastewater using zeolite clinoptilolite type natural and artificial, natural zeolite activated manganese oxide by artificial means from manganese sulfate. The experimental development was held in the Company PMS S.A.S. and involved three major stages: initial characterization of water, pre-treatment and treatment with zeolite. The first stage of characterization is performed to determine nonconforming parameters with the current regulations. The pre waste treatment with poly aluminum chloride (PAC) as coagulant and cationic polyacrylamide as a flocculants removes pollutants and prevents water from reaching very organic and solid load suspended when filtered by the zeolite to not causes rapid saturation.